Força da musculatura do assoalho pélvico segundo o tipo de parto - Silva, Cristiane Dallastra Candido da (2022)
Introduction: Pregnancy, laboring and delivering can influence the pelvic floor muscles, which can lead to reduced strength and future transient or permanent diseases. Objectives: Evaluating the PFMS of women between 4 and 6 months normal and cesarean section postpartum of a public hospital. Methods: A cross-sectional clinical study to assess PFMS using the perineometer and the pelvic floor strength (PFA) assessment test. The contraction measured by perineometry was classified as: zero - no contraction, one - mild, two - moderate, three - normal and sustained. The measurement by AFA ranged from zero to five, where zero demonstrates absence of perineal contraction and five represents present perineal function sustained for more than five seconds. Strength was measured in 183 women, divided into three groups: Vaginal delivery group VDG (n=61), Cesarean delivery group CDG (n=61) and Nulliparous group NG (n=61). The independent variable was the mode of delivery and the dependent variable was the pelvic floor muscle strength. Comparisons between delivery modes were performed using the Kruskal-wallis and Many-Whitney U tests. The chi-square test was used to verify the association between birth condition, PFMS and other covariates. Results: The highest prevalence of inadequate outcome was observed among participants who underwent normal delivery (perineometry = 90.2% and PFA = 36.1%), followed by cesarean sections (perineometry = 78.7% and PFA = 21.3%) and nulliparous women (perineometry = 36.1% and PFA = 4.9%).